THE ACHIEVEMENT OF MALE FAMILY PLANNING PROGRAM: VASECTOMY IN DLINGO AND SEWON DISTRICTS, BANTUL REGION - Novitrisia Widowati; Agus Joko Pitoyo; Agus Hadna (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
One of male contraception methods in family planning program is vasectomy; however, its achievement has been still far behind due to several obstacles in its implementation. In Bantul, Dlingo is a rural sub-district with the highest achievement of vasectomy participants during the last three years (2007-2009). Such a condition is contrary to that found in Sewon as an urban sub-district. This study aimed to identify factors influencing the differences in the achievement, and its results would be beneficial in improving the participation level of vasectomy male contraception. This was a qualitative study comparing the conditions of the two sub-districts through the use of primary and secondary data. Subjects in the research considered information accuracy and validation; hence, its number was subject to the expected results. Data validity testing was performed by utilizing triangulation. Data analysis techniques involved data reduction, presentation, and verification, or tentative conclusion drawing possibly answered the research problem. The result of the research which influenced vasectomy male participation involved un-wealthy or limited economic conditions. This was supported by officers’ attitude and behavior, peer support, public/ religious leaders and community association that actively provided greater contribution in improving participation, and association as the media of socialization and motivation. The results recommended data updating, dialogues with public leaders/religious leaders, and also socialization concerning vasectomy. Tomaintain and increase the male contraception participation level, it is necessary to perform establishment, activation, supervision on the association of male contraception participants, with regard to welfare improvement. Recognition awarded to vasectomy participants and Family Planning Field Officer for their achievement is also necessary.Keywords: Vasectomy, Socialization, Recognition